2022
DOI: 10.1002/pros.24425
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer grade downgrading at time of prostatectomy provides risk‐stratification insight into future tumor behavior after prostatectomy

Abstract: Background: Prostate biopsy (Bx) sampling-based diagnosis of prostate cancer (PCa) has well-described inaccuracy when compared against whole gland analysis upon prostatectomy. Although upgrading of PCa Grade Group (GG) is often described, the occurrence and prognostic implications of downgrading PCa GG at the time of radical prostatectomy (RP) is less understood. Our objective was to evaluate whether downgrading PCa GG at the time of RP was associated with future tumor behavior. Methods:The SEER database was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
2
2
0
Order By: Relevance
“…The downgrading rates in our study (51% for any downgrading and 43% for significant downgrading) were in agreement with the rates reported by Wenzel et al (50% for any downgrading and 44% for significant downgrading) [15]. Previously reported downgrading rates in other tertiary-care-based RP cohorts of patients with Gleason grades of 4 ranged from 45% to 61.5% [26][27][28]. However, these rates cannot be directly compared to those in previous downgrading reports, since no other reports focused only on biopsied high-risk prostate cancer patients while also including Gleason grade group 5.…”
Section: Discussionsupporting
confidence: 92%
“…The downgrading rates in our study (51% for any downgrading and 43% for significant downgrading) were in agreement with the rates reported by Wenzel et al (50% for any downgrading and 44% for significant downgrading) [15]. Previously reported downgrading rates in other tertiary-care-based RP cohorts of patients with Gleason grades of 4 ranged from 45% to 61.5% [26][27][28]. However, these rates cannot be directly compared to those in previous downgrading reports, since no other reports focused only on biopsied high-risk prostate cancer patients while also including Gleason grade group 5.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, higher GPS results were associated with greater risk of all relevant outcomes in both univariable and multivariable analyses that included key clinical factors. This confirms the finding in RP cohorts that a genomic assessment of tumor aggressiveness provides additional information beyond traditional clinical factors such as Gleason grade group (which is highly prone to reclassification 32 , 33 , 34 ), PSA (which is variable and affected by medications and other factors 35 , 36 ), or clinical T stage via digital rectal examination (the reproducibility of which has never been established). These results are also consistent with outcomes from the study of the GPS assay in patients post-RT from a Veterans Affairs cohort.…”
Section: Discussionsupporting
confidence: 78%
“…16 Despite the increasing trend in the use of AS, contemporary series revealed that almost 22%-33% of all RP surgeries were still performed for GG1 disease at prostate biopsy. 17,18 Therefore, it is of utmost importance to predict the patients who would most likely upgrade and benefit from active treatment in cases with a biopsy GG1 disease.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years AS was also recommended to highly selected patients with GG 2 disease by the American Society of Clinical Oncology (ASCO) and European Association of Urology (EAU) guidelines 14,15 A Surveillance, Epidemiology, and End Result Program (SEER) analysis revealed that the use of AS increased from 22% in 2004–2005 to 50% in 2014–2015 in cases with GS ≤ 6 and increased from 9% in 2004–2005 to 13% in 2014–2015 for patients with a GS ≥ 7 16 . Despite the increasing trend in the use of AS, contemporary series revealed that almost 22%–33% of all RP surgeries were still performed for GG1 disease at prostate biopsy 17,18 . Therefore, it is of utmost importance to predict the patients who would most likely upgrade and benefit from active treatment in cases with a biopsy GG1 disease.…”
Section: Discussionmentioning
confidence: 99%